PESAN MORAL RANGGAWARSITA DALAM KALATIDHA DAN SERAT JAKA LODHANG - Marsih, Linusia (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2011)
Abstract. Through Javanese lyrical poem â€œmacapatâ€, Ranggawarsita delivered his social critiques toward the Soloâ€™s royal family disgraceful behaviors in the middle of XIX century. The substance of the critiques, however, is still actual for the Indonesia in the Reformation Order since this order practices corruption, collusion, and nepotism worse. Ranggawarsitaâ€™s moral messages that are still actual up to the present are: (1) the lack of role model of leadershipâ€™s behaviors resulting in country depravity; (2) intelligence without morality causing misfortune; (3) no matter how happy the forgetful people, being happier those who are alert and still remember; sticking to the truth one to be despite his surrounding doing greedy; (4) the religious leaders and intellectuals having to be standing up for temptation. Key words: moral message, macapat, coruption, state leaders, cultural resistence